EFFECTIVENESS OF THE USE OF ELEMENTS OF SPORTS EXERCISES IN THE DEVELOPMENT OF QUALITIES OF SPEED AND AGIETY IN VOLLEYBALL - Doniyor Abdusalomov (Bright Mind Publishing, 2025)
The development of speed and agility is one of the key components in the training of volleyball players, particularly in enhancing their ability to perform dynamic movements such as quick directional changes, jumps, and rapid reactions. This article examines the effectiveness of using sports exercise elements—drawn from both general physical training and specialized drills—in developing these qualities in volleyball players. Based on the analysis of current scientific literature, field observations, and practical implementation in training settings, the study highlights specific training methods, including plyometric exercises, sprint drills, coordination tasks, and complex movement patterns that simulate in-game situations. The findings suggest that integrating sports exercise elements within volleyball training programs not only enhances athletic performance but also contributes to the reduction of injury risks through improved neuromuscular coordination and muscle elasticity. The article is aimed at coaches, physical education teachers, and sports science students seeking to deepen their understanding of speed and agility training in volleyball within the context of Uzbek sports development.
Keywords: Speed, agility, volleyball, sports exercises, physical training, coordination, plyometrics, athletic performance, training methods, Uzbekistan.